Persepsi Wanita Tani Terhadap Dampak Program Gerakan Pembangunan Desa Terpadu (Gerbang Sadu) Mandara (Kasus pada Kelompok Tani Pelita Hati II di Desa Bebandem, Kecamatan Bebandem, Kabupaten Karangasem) - I DEWA GEDE WIPA WIRA UTAMA; I GEDE SETIAWAN ADI PUTRA; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
Abstract Perception of Women Farmers on The Impact of Gerakan Pembangunan Desa Terpadu (Gerbang Sadu) Mandara Program (Case in Pelita Hati II Farmer Groups Bebandem Village, Bebandem District, Karangsem Regency) Poverty remains a serious problem in the Bali Province. One of the Government of Bali’s efforts to reduce poverty rate by initiating Gerakan Pembangunan Desa Terpadu (Gerbang Sadu) Mandara program in a village that have the level of poverty above 35%. One of the village is Bebandem Village with the poverty rate at 39,43%. The aim of this research is to determine the impact in the term of management, economic, and social aspects. This research was conducted in Pelita Hati II Farmer Groups, Bebandem Village, Bebandem District, Karangasem Regency for 10 months from September 2014 until June 2015. There are 10 members of population and wholly be used as respondents using cencus technique. The method of data analysis using qualitative descriptive analysis. The results of research shows that the impact of Gerbang Sadu Mandara program in the terms of management aspect is considered relatively good (65,95%). The planning indicators is considered relatively good (64,50%), the organizing indicators is considered relatively good (65,00%), the implementation indicators is considered relatively good (66,30%), and the supervision indicators is considered relatively good (68,00%). The impact of Gerbang Sadu Mandara program in the terms of economic aspect have an impact on the increase in income members of the group. The impact of Gerbang Sadu Mandara program in the terms of social aspect is considered relatively good (63,00%). Interaction indicators among members is considered relatively good (62,00%). Interaction indicators among members and the group is considered relatively good (59,50%), and interaction indicators among members and village institution is considered relatively good (68,00%). Keywords: Impact, Program, Gerbang Sadu Mandara, Farmers Group